2018
DOI: 10.1002/cncr.31758
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of childhood acute lymphoblastic leukemia with delayed first intrathecal therapy and omission of prophylactic cranial irradiation: Results of the TPOG‐ALL‐2002 study

Abstract: Background To eliminate cranial irradiation (CrRT)–related sequelae and to minimize the adverse impact of traumatic lumbar puncture (TLP) with blasts, the Taiwan Pediatric Oncology Group (TPOG) introduced a modified central nervous system (CNS)–directed regimen characterized by delayed triple intrathecal therapy (TIT) and the omission of CrRT for all children with newly diagnosed acute lymphoblastic leukemia (ALL). Methods This study compared the treatment outcomes of patients overall and patients with a non–C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…A comparison of contemporary trials of limited use and complete omission of prophylactic cranial irradiation shows similar rates of event‐free survival and CNS control (Table ). The likelihood of 5‐year event‐free survival and the cumulative risk of an isolated CNS relapse ranged from 72% to 89% and from 1% to 4.1%, respectively, in the 4 studies that omitted irradiation, whereas they ranged from 85% to 87.3% and from 1.4% to 2%, respectively, in the 3 trials in which up to approximately 10% of the patients were irradiated and from 82.5% to 85% and from 0.9% to 1.3%, respectively, when more than 10% were irradiated . Indeed, a 2016 meta‐analysis of more than 16,000 patients enrolled in clinical trials of 10 cooperative childhood ALL study groups indicated that prophylactic cranial irradiation had no impact on the overall survival or the cumulative risk of death, any adverse event, isolated CNS relapse, or combined CNS relapse in any subgroup of high‐risk patients with the exception of those with overt CNS leukemia (CNS‐3 status, 5 or more leukocytes per microliter with blasts) .…”
Section: Characteristics and Treatment Outcomes Of Selected Contempormentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of contemporary trials of limited use and complete omission of prophylactic cranial irradiation shows similar rates of event‐free survival and CNS control (Table ). The likelihood of 5‐year event‐free survival and the cumulative risk of an isolated CNS relapse ranged from 72% to 89% and from 1% to 4.1%, respectively, in the 4 studies that omitted irradiation, whereas they ranged from 85% to 87.3% and from 1.4% to 2%, respectively, in the 3 trials in which up to approximately 10% of the patients were irradiated and from 82.5% to 85% and from 0.9% to 1.3%, respectively, when more than 10% were irradiated . Indeed, a 2016 meta‐analysis of more than 16,000 patients enrolled in clinical trials of 10 cooperative childhood ALL study groups indicated that prophylactic cranial irradiation had no impact on the overall survival or the cumulative risk of death, any adverse event, isolated CNS relapse, or combined CNS relapse in any subgroup of high‐risk patients with the exception of those with overt CNS leukemia (CNS‐3 status, 5 or more leukocytes per microliter with blasts) .…”
Section: Characteristics and Treatment Outcomes Of Selected Contempormentioning
confidence: 99%
“…Encouraged by these early findings, most study groups now restrict prophylactic cranial irradiation to patients at high‐risk for CNS relapse, and some, such as the Taiwan Pediatric Oncology Group (TPOG), as reported in this issue of Cancer , have eliminated this treatment modality altogether . A comparison of contemporary trials of limited use and complete omission of prophylactic cranial irradiation shows similar rates of event‐free survival and CNS control (Table ).…”
Section: Characteristics and Treatment Outcomes Of Selected Contempormentioning
confidence: 99%
See 1 more Smart Citation
“…The girl received chemotherapy according to the Taiwan Pediatric Oncology Group (TPOG) 2013-ALL-SR protocol, and spinal tap and triple intrathecal therapy was performed 7 to 10 days after chemotherapy. [ 3 ] No leukemic cells were found in the cerebral spinal fluid and the patient commenced prophylactic antibiotic and antifungal therapies with levofloxacin and micafungin on January 14th, when her leukocyte count was less than 1 × 10 9 cells/μl. She later developed febrile neutropenia on January 20th, and was administered teicoplanin and meropenem post collection of her blood for culture.…”
Section: Introductionmentioning
confidence: 99%
“…For the management of pediatric ALL, different treatment protocols have been developed since years. [ 10 , 11 ] Treatment regimens comprised of multiple cytotoxic drugs including doxorubicin, cytarabine, methotrexate, vincristine, and etoposide. However, ALL children with co-existing DS may be more vulnerable to toxic side effects.…”
Section: Introductionmentioning
confidence: 99%